Database management for forestry literature in the Asia-Pacific region - Soeripto, S.W. (1998)
Databases for forestry literature in the Asia Pacific Region have not been fully developed. The needs for establishing good database is not well understood by all levels of management at many forestry organizations. Some aspects which affect databases management including management support, organizational structure, information technology, data collection, and information delivery are briefly discussed. In addition a short list of forestry related CD-ROM databases and forestry web sites is included at the end of this paper.